iSIS - enhancement of GPA and CGPA calculation without hard-coded source code utilizing oracle DBMS / Zamri Abu Bakar - Abu Bakar, Zamri (2006)
Integrated Student Information System (iSIS) is comprehensive in nature, encompassing the needs of a multitude of user groups and it is all a trans-active web based application. iSIS also has been developed to support Bahagian Hal Ehwal Akademik (HEA) in running student information more easier and clearer way. It was also designed and developed to run all process about the student information. Utilizing object based and three-tier Client Server technology, iSIS has developed system encompassing the complete student life cycle student, from Intake to Convocation and Alumni. Inline with University Administration inspiration to make UiTM as a world class University, PSMB plans to add several enhancements into the system. The main enhancement planed for iSIS is to change the RDBMS platform from SQL Server 2000 to the ORACLE. Since the enhancement require process reengineering, it will also effects GPA and CGPA calculation module. In order to maintain the academic excellence, the academic regulation needs to review from time to time. Whenever there are changes in academic regulation, the changes must be reflected in iSIS. Since the GPA and CGPA calculation module in iSIS uses a hard-coded approach, the maintenance of the module is difficult. The new approach will be introduced with development a new flexible web application on utilizing ORACLE DBMS without or minimizes hard-coded source code.